Neuroprotective therapies for glaucoma - Song W; Huang P; Zhang C (Drug Design, Development and Therapy, 2015)
Wei Song, Ping Huang, Chun Zhang Department of Ophthalmology, Peking University Third Hospital, Beijing, People’s Republic of China Abstract: Glaucoma is the second leading cause for blindness worldwide. It is mainly caused by glaucomatous optic neuropathy (GON) characterized by retinal ganglion cell loss, which leads to visual field defect and blindness. Up to now, the main purpose of antiglaucomatous therapies has been to lower intraocular pressure (IOP) through surgeries and medications. However, it has been found that progressive GON is still present in some patients with effective IOP decrease. Therefore, risk factors other than IOP elevation, like neurotrophin deprivation and excitotoxicity, contribute to progressive GON. Novel approaches of neuroprotection may be more effective for preserving the function of the optic nerve. Keywords: glaucoma, glaucomatous optic neuropathy, retinal ganglion cells, neuroprotection